Exciton Relaxation Dynamics in Photo-Excited CsPbI(3) Perovskite Nanocrystals - Liu, Qinghui (Sci Rep, 2016)
The exciton relaxation process of CsPbI(3) perovskite nanocrystals (NCs) has been investigated by using transient absorption (TA) spectroscopy. The hot exciton relaxation process is confirmed to exist in the CsPbI(3) NCs, through comparing the TA data of CsPbI(3) NCs in low and high energy excitonic states. In addition, the Auger recombination and intrinsic decay paths also participate in the relaxation process of CsPbI(3) NCs, even the number of exciton per NC is estimated to be less than 1. Excitation intensity-dependent TA data further confirms the existence of Auger recombination. Meanwhile, the spectral data also confirms that the weight of hot exciton also increase together with that of Auger recombination at high excitation intensity when CsPbI(3) NCs in high energy excitonic states.